A catalytic mechanism investigation of TiF3 on hydriding/dehydriding properties of Mg85Cu5Ni10 alloy. Issue 15 (1st March 2021) - Yin, Yi; Qi, Yuanhong; Li, Bo; Gu, Hu; Zhao, Jinghui; Ji, Liqiang; Zhang, Bo; Yuan, Zeming; Zhang, Yanghuan
Abstract : The dehydrogenation activation energy E a (de) of Mg85 Cu5 Ni10 is reduced to 81.462 from 116.767 kJ mol −1 by adding 6 wt% TiF3 . Abstract : In this research, Mg85 Cu5 Ni10 – x wt% TiF3 ( x = 0, 2, 4, 6, 8) alloys were synthetized via ball milling and the catalytic mechanism of TiF3 on hydrogenation and dehydrogenation of Mg85 Cu5 Ni10 was studied. The microstructure, hydriding/dehydriding kinetics and thermodynamics of the alloys were discussed in detail. The TiF3 catalyzed alloys have faster hydriding/dehydriding kinetics and lower thermodynamic stability. After hydrogen absorption and desorption, TiF3 decomposes into TiH2 and MgF2 . TiF3, TiH2 and MgF2 promote to forming crystal defects, dislocations, grain boundaries and nanocrystals which are advantageous to speeding up the rate of hydrogen absorption and desorption. The dehydrogenation activation energy E a (de) and dehydrogenation enthalpy Δ H (de) are reduced to 81.462 from 116.767 kJ mol −1 and 72.456 from 93.372 kJ mol −1 respectively by 6 wt% TiF3 . An appropriate amount of TiF3 can improve the hydriding/dehydriding kinetics and thermodynamics of Mg85 Cu5 Ni10 .